KUALITAS PELAYANAN JASA TRANSPORTASI ONLINE PADA PT KARYA ANAK BANGSA (GO-JEK) DI KOTA PEKANBARU - Suhanda, Nathasa; Sadad, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Pekanbaru city has two twowheeled public transportation, namely application and conventional. NadiemMakariem keep up with technology by creating Ltd AplikasiKaryaAnakBangsa (Go-jek) Indonesia namely companies that provide technology services for online motorbike transportation services. But until now it has not been in accordance with the regulations that have been set by Ltd Go-jek so that there are various complaints by consumers in receiving services by drivers of motorcycles in Pekanbaru city. The purpose of this research is to find out how the quality of online transportation services is on LdtAplikasiKaryaAnakBangsa(Go-jek) in Pekanbaru city and to find the factors that hinder the service quality. The theory used in this research is Sinambela theory who have indicators such as transparency, accountability, conditional, participatory, equal rights, balance of rights and obligations. The research method used is qualitative research. This research was used observation, interviews, literature studies and online data search. Selection of research informant using purposive sampling techiques and for source of information and data analysis using triangulation techniques. The result of this research shows thet quality of motorbike driver services in the city of Pekanbaru has been maximized and effective because regulations and driver requirements are increasingly tightened to get the quality expected by consumers.Keywords: Service Quality, Transportation, Go-jek